PENGARUH CAR, NPL, NIM, BOPO, LDR DAN SUKU BUNGA SBI TERHADAP ROA BANK BUMN PERIODE TAHUN 2009-2018 - Dini, Novia; Manda, Gusganda Suria (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2020)
This study aims to determine the effect of CAR, NPL, NIM, BOPO, LDR and SBI Interest Rates on ROA of Bank BUMN for the period of   2009-2018. Hypothesis testing of this study uses multiple linear regression analysis. This research was conducted at  the BUMN Bank in the period 2009-2018. The research  was population is 4 BUMN Bank. The sample technique used in this study is saturated sampel technique. The results showed CAR did not influence ROA, NPL have positive effect on the ROA, NIM have  positive effect on the ROA, BOPO have negative effect on the ROA, LDR have negative effect on the ROA, SBI Interest Rate have positive effect on the ROA.